2005
DOI: 10.1038/sj.onc.1208433
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles for the coactivators CBP and p300 on TCF/β-catenin-mediated survivin gene expression

Abstract: The inhibitor of apoptosis (IAP) protein survivin is highly expressed in cancers, but not in normal differentiated tissues. TCF/b-catenin signaling has been reported to participate in the regulation of survivin transcription in colon cancer. We have recently characterized ICG-001, a small molecule specific inhibitor of the b-catenin/ Creb-binding protein (CBP) interaction. Inhibition of the b-catenin/CBP interaction represses a subset of TCF/bcatenin-mediated transcription. ICG-001 potently inhibits survivin g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
300
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(316 citation statements)
references
References 45 publications
12
300
2
1
Order By: Relevance
“…HGFR activation protects from apoptosis in several tumor in vitro models (Bowers et al, 2000;Fan et al, 2000Fan et al, , 2005Gao et al, 2001;Zeng et al, 2002;Derksen et al, 2003;Lal et al, 2005), and activation of b-catenin promotes the transcription of antiapoptotic genes (Dihlmann et al, 2005;Kim et al, 2005;Ma et al, 2005) and was associated with increased tumor cell survival in CRC (Ireland et al, 2004;Ougolkov et al, 2004). However, a proapoptotic role of HGF (Arakaki et al, 1998;Matteucci et al, 2003;Rasola et al, 2004) and b-catenin (Kim et al, 2000;van Gijn et al, 2001;Edlund et al, 2005) was also reported in several models.…”
Section: Discussionmentioning
confidence: 99%
“…HGFR activation protects from apoptosis in several tumor in vitro models (Bowers et al, 2000;Fan et al, 2000Fan et al, , 2005Gao et al, 2001;Zeng et al, 2002;Derksen et al, 2003;Lal et al, 2005), and activation of b-catenin promotes the transcription of antiapoptotic genes (Dihlmann et al, 2005;Kim et al, 2005;Ma et al, 2005) and was associated with increased tumor cell survival in CRC (Ireland et al, 2004;Ougolkov et al, 2004). However, a proapoptotic role of HGF (Arakaki et al, 1998;Matteucci et al, 2003;Rasola et al, 2004) and b-catenin (Kim et al, 2000;van Gijn et al, 2001;Edlund et al, 2005) was also reported in several models.…”
Section: Discussionmentioning
confidence: 99%
“…Sumoylation of the CRD1 domain of p300 was shown to mediate this repressor activity. In vitro and in vivo studies suggested that a direct binding of HDAC6 to SUMO-CRD1 could be responsible for the observed transcription repression by the CRD1 domain of p300 (Girdwood et al, 2003), and further investigations suggested that this mechanism could be involved in the repression of at least two cellular genes (Ling and Lobie, 2004;Ma et al, 2005).…”
Section: Nuclear Targets Of Hdac6mentioning
confidence: 98%
“…27 It has been shown that it plays a very distinct role in survivin gene transcription. 28 The direct inhibition of survivin expression by curcumin was shown very recently in adult T-cell leukemia. 8 Also our data (Wolanin et al, accepted to Mol.…”
Section: Discussionmentioning
confidence: 99%